Energy Analysis of Single and Dual Pcm Trombe Wall Configurations for Indoor Heating Considering Dynamic Scenarios in Summer/Winter of Two Different Climate Regions Through Cfd Modeling - Rivera-Aguilera, D (Elsevier Ltd, 2024)
Passive systems to achieve thermal comfort in buildings are crucial to overcome the current climate crisis. Direct solar gain systems, such as the Trombe Wall (TW), can significantly reduce heating and cooling demands of buildings, generating substantial economic and environmental value. Although Phase Change Materials (PCMs) have widely demonstrated to enhance the energy storage performance of TW-systems, there still exist a search for the most thermally efficient PCM configuration given specific climate conditions and building demands. The present work numerically studies the energy performance of single- and dual-layer PCM-TW configurations for the heating of a semi-open room in four different climatic scenarios, resulting in a total of 28 cases. Three commercial salt-hydrate PCMs with different melting points, SP21, SP27, and SP31, are investigated in three scenarios for each single- and dual-PCM configuration. Representative days of hot-summer and cold-winter scenarios of two climatic regions with a large difference in latitude, classified as cold arid desert (CR1) and mild temperature cold summer (CR2), are studied. The day-to-night dynamic analysis is performed by an in-house CFD model with the k-ω SST turbulent model, the net discrete thermal radiation method, and the liquid fraction phase change model for the PCMs. The results indicate that the PCM-configurations with the best combined performance were: for CR1, the Single-PCM with SP31 increased the average air temperature by 21 % in winter, and decreased it by 9 % in summer; while for CR2, the Dual-PCM SP26/SP31 increased the average air temperature by 31 % in winter, and decreased it by 5 % in summer. Overall, the PCMs increased the energy stored by the wall at cost of decreasing the heat provided to the building, which beneficially homogenized the heat fluxes through day to night. © 2024 Elsevier Ltd